Analisis Pengaruh Current Ratio, Debt To Equity Ratio, dan Return On Asset Terhadap Return Saham Pada Perusahaan Pertambangan di Bursa Efek Indonesia - Erari, Anita (Jurnal Manajemen Bisnis, 2014)
This study aimed to analyze the influence of Current Ratio, Debt to Equity Ratio and Return On Asset on stock returns simultaneously and partially. Objects of research are amining companies listed on the Indonesia Stock Exchange. Data used to analysis is the financial statements (Balance Sheet and Income Statement) 2010-2013, using the technique of multiple regression analysis and ratios. It was concluded from the results of data analysis that: variable Current Ratio, Debt to Equity Ratio and Return On Asset simultaneously affect the stock return to the calculated F value of 4.141 with a significance level of less than 0.05. Current Ratio and Debt to Equity partially no effect on stock returns, only a return on assets that have an influence on stock returns with t count of 3,107 with significance value of 0.004, so the dominant variable effect on stock returns is Return On Asset.